FROM “TEXT FOR LOCATION” TO “NO PHONE ON THE DANCE FLOOR”: NEGOTIATING VISIBILITY IN UNDERGROUND ELECTRONIC/DANCE MUSIC - Yang, Stephen (AoIR Selected Papers of Internet Research, 2023)
The mediation of mobile and social media technologies has reshaped how people imagine, understand, and, in turn, calibrate the visibility of their self-expression, information sharing, and relationship-building. This paper presents a case study of how promoters and attendees in underground electronic/dance music culture (EDMC) maintained the boundaries of the “underground” by co-constructing norms of mobile and social media use. Drawing upon 20 nights of field observations at live music events and 27 semi-structured interviews with promoters and attendees, I highlighted two scenarios in which promoters and attendees leveraged the spatial and temporal affordances of mobile and social media to calibrate their visibility. First, the last-minute and indirect sharing of event location afforded the community to bar outsiders from entering while allowing insiders to authenticate themselves by navigating to their gatherings. Second, the dialectical shaping between promoters’ venue policies and attendees’ folk theories of phone etiquette maintained a reduced level of mobile media use at such gatherings. These practices brought to light how mobile and social media afford new spatial-temporal conditions of visibility and bring forth new possibilities for people to not only manage – but play with visibility.